Agreement between Medicare pharmacy claims, self‐report, and medication inventory for assessing lipid‐lowering medication use. Issue 7 (29th January 2016) - Colantonio, Lisandro D.; Kent, Shia T.; Kilgore, Meredith L.; Delzell, Elizabeth; Curtis, Jeffrey R.; Howard, George; Safford, Monika M.; Muntner, Paul
Abstract: Background: Medicare claims have been used to study lipid‐lowering medication (LLM) use among US adults. Methods: We analyzed the agreement between Medicare claims for LLM and LLM use indicated by self‐report during a telephone interview and, separately, by a medication inventory performed during an in‐home study visit upon enrollment into the REasons for Geographic And Racial Differences in Stroke (REGARDS) study. We included REGARDS participants ≥65 years enrolled in 2006–2007 with Medicare pharmacy benefits (Part D) from 120 days before their telephone interview through their medication inventory ( n  = 899). Results: Overall, 39.2% and 39.5% of participants had a Medicare claim for an LLM within 120 days prior to their interview and medication inventory, respectively. Also, 42.7% of participants self‐reported using LLMs, and 41.8% had an LLM in their medication inventory. The Kappa statistic (95% confidence interval [CI]) for agreement of Medicare claims with self‐report and medication inventory was 0.68 (0.63–0.73) and 0.72 (0.68–0.77), respectively. No Medicare claims for LLMs were present for 22.1% (95%CI: 18.1–26.6%) of participants who self‐reported taking LLMs and 18.9% (15.1–23.3%) with LLMs in their medication inventory. Agreement between Medicare claims and self‐report was lower among Black male individuals (Kappa = 0.34 [95%CI: 0.14–0.54]) compared with Black female individuals (0.70 [0.61–0.79]), White male individuals (0.65 [0.56–0.75]), and White female individuals (0.79 [0.72–0.86]). Agreement between Medicare claims and the medication inventory was also low among Black male individuals (Kappa = 0.48 [95%CI: 0.29–0.66]). Conclusions: Although substantial agreement exists, many Medicare beneficiaries who self‐report LLM use or have LLMs in a medication inventory have no claims for these medications. Copyright © 2016 John Wiley & Sons, Ltd.